2001
DOI: 10.1067/mva.2001.120037
|View full text |Cite
|
Sign up to set email alerts
|

Impact of exclusion criteria on patient selection for endovascular abdominal aortic aneurysm repair

Abstract: Most infrarenal AAAs (66%) can be treated with endovascular devices currently available commercially or through US Food and Drug Administration-approved clinical trials. However, patients who are at high risk for surgery and might benefit most from endovascular repair are less likely to qualify for the procedure (49%). Men (70%) are more likely than women (40%) to meet the anatomic criteria for endografting. Difficulties with vascular access and attachment site geometry predominate as reasons for exclusion. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
217
1
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(235 citation statements)
references
References 20 publications
6
217
1
9
Order By: Relevance
“…The data from our systematic review do not suggest that the proportion of women morphologically suitable for EVAR has improved since earlier this century. 6,7 However, the operative mortality in both men and women has fallen substantially since a 2010 systematic review, 9 particularly for open repair; although 30-day operative mortality remains almost twice as high in women as in men. Some of the reduction in operative mortality in women might have come at the expense of the high proportion of women (a third) who are assigned to a non-intervention policy; although, the literature on non-intervention policy remains sparse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data from our systematic review do not suggest that the proportion of women morphologically suitable for EVAR has improved since earlier this century. 6,7 However, the operative mortality in both men and women has fallen substantially since a 2010 systematic review, 9 particularly for open repair; although 30-day operative mortality remains almost twice as high in women as in men. Some of the reduction in operative mortality in women might have come at the expense of the high proportion of women (a third) who are assigned to a non-intervention policy; although, the literature on non-intervention policy remains sparse.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 However, data from the large Medicare database in the USA suggest that this relative difference in 30-day mortality between EVAR and open repair is observed for both men and women, even though the absolute mortality was higher in women than men. 8 An earlier systematic review, 9 including studies published by July, 2009, showed that for elective open repairs the operative mortality (30 day or in-hospital) was 7·6% for women versus 5·1% for men.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, EVAR has technical limitations caused by the present stent-graft system construction and the indication depends on AAA morphology. Not all AAAs could be endovascularly treated [21][22][23] . That is why all questions in preoperative decision as to the type of treatment are connected with the patient risk and AAA morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Open surgery was indicated in 115 patients (n = 38 %), 128 patients (n = 43 %) were treated endovascularly [16][17][18][19][20] . Indication for elective treatment and the way of repair were determined according to patients' life expectancy, condition (ASA classification) and AAA morphlogy analyses 7,8,[21][22][23] ( Fig. 2).…”
Section: Methodsmentioning
confidence: 99%
“…A retrospective analysis of 307 patients showed that up to 34 % of patients do not meet the anatomical requirements for EVAR, with 47 % of those being due to an insufficient diameter of the iliac arteries and 10 % due to high torsion of the pelvic axis [36]. The diameter of the common iliac artery should be at least 2 mm smaller than the prosthesis diameter to achieve adequate anchoring through moderate oversizing.…”
Section: Iliac Arteriesmentioning
confidence: 99%